3.0-T closed MR-guided microwave ablation for HCC located under the hepatic dome: a single-center experience. (31st December 2022) - Xu, Kaihao; Li, Zhaonan; Wang, Chaoyan; Tian, Chuan; Jiao, Dechao; Han, Xinwei; Yan, Yan
Abstract: Purpose: To analyze the clinical safety and efficacy of 3.0-T closed MR-guided microwave ablation (MWA) for the treatment of HCC located under the hepatic dome. Methods: From May 2018 to October 2020, 49 patients with 74 HCCs located under the hepatic dome underwent MWA using 3.0-T closed MR guidance. The technical success rate, operative time, complete ablation (CA) rate, complications, local tumor progression (LTP), tumor-free survival (TFS) and overall survival (OS) were examined. Routine blood analysis, liver/kidney function and alpha fetoprotein (AFP) and protein induced by vitamin k absent or antagonist (PIVKA) levels were compared before and 2 months after MWA. Results: All patients underwent MWA successfully, including 10 patients who underwent general anesthesia. The technical success rate was 100% without major complications. The CA rate was 95.9% (71/74) at the 2-month evaluation. The LTP rate was 2.7% during the median follow-up of 17.8 months (range: 4–43 months); the 6-, 12-, 18-month TFS rates were 97.8, 90.6, 68.1%, respectively, and the 6-, 12-, 18-month OS rates were 100, 97.6, 92.1%, respectively. There were no significant changes in routine blood tests and liver/kidney function ( p > 0.05), while the AFP and PIVKA level decreased significantly at 2 months ( p < 0.05). Conclusion: 3.0-T MR-guided MWA is safe and feasible for HCC lesions located under the hepatic dome.